2015
DOI: 10.3390/v7102873
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modal Imaging with a Toolbox of Influenza AReporter Viruses

Abstract: Reporter viruses are useful probes for studying multiple stages of the viral life cycle. Here we describe an expanded toolbox of fluorescent and bioluminescent influenza A reporter viruses. The enhanced utility of these tools enabled kinetic studies of viral attachment, infection, and co-infection. Multi-modal bioluminescence and positron emission tomography–computed tomography (PET/CT) imaging of infected animals revealed that antiviral treatment reduced viral load, dissemination, and inflammation. These new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 25 publications
0
55
0
Order By: Relevance
“…We have previously shown that this limitation can be circumvented by using replication-competent viruses harboring fluorescent reporter genes whose expression can be monitored and quantified directly (2,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). In addition, those reporter-expressing viruses have been demonstrated to be valuable assets for the screening and the identification of antivirals and/or host factors with antiviral activity (2,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Since the expression and activity of Venus and NLuc are dependent on BIRFLU infection, the presence of both reporters in infected cells (Venus) or in the culture supernatants (NLuc) can be used as a valid surrogate of viral replication.…”
Section: Birflu Reporter Gene Expression Levels Correlate With Dose-dmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that this limitation can be circumvented by using replication-competent viruses harboring fluorescent reporter genes whose expression can be monitored and quantified directly (2,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). In addition, those reporter-expressing viruses have been demonstrated to be valuable assets for the screening and the identification of antivirals and/or host factors with antiviral activity (2,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Since the expression and activity of Venus and NLuc are dependent on BIRFLU infection, the presence of both reporters in infected cells (Venus) or in the culture supernatants (NLuc) can be used as a valid surrogate of viral replication.…”
Section: Birflu Reporter Gene Expression Levels Correlate With Dose-dmentioning
confidence: 99%
“…The modification of viral segments for the incorporation of reporter genes, such as fluorescent or luciferase proteins, in replication-competent IAV has been a crucial technological advance in the field. Genetically modified IAV expressing reporter genes is an excellent tool for the tracking of viral infection in vitro and in vivo, providing a robust quantitative readout of viral replication (2,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). In addition, this readout is compatible with high-throughput screening (HTS) technologies and useful to assess viral infection in cultured cells and animal models without the use of laborious secondary approaches to identify the presence of the virus in infected cells and/or animals (2,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We probed each successive step that occurs early in the infectious cycle, beginning with viral attachment. Wild-type or edited cells were incubated with bioluminescent virions (PASN) that package nanoluciferase into the viral particle (Tran et al, 2015). Cells were incubated at 4˚C to enable binding but prevent internalization of virions, and luciferase activity was assayed from the bound virions.…”
Section: Eps8 Functions Post-fusion But Before Viral Gene Expression mentioning
confidence: 99%
“…The recombinant influenza A reporter viruses WSN PASTN (Tran et al, 2013), A/California/04/2009 PASTN (H1N1, CA04 PASTN) (Karlsson, 2015), WSN PASN (Tran et al, 2015), WSN with the polymerase from A/green-winged teal/ OH/175/1983 (H2N1) encoding PB2 S590/R591/K627 (S009-SRK PASTN) (Tran et al, 2015), B/Brisbane/60/2008 (B/Brisbane) PASTN, and FVG-R (Hao et al, 2008) were rescued using the influenza virus reverse genetics system and prepared as previously described. WSN PASN was further purified by centrifugation through a 20% sucrose cushion to remove contaminating luciferase present in the media (Tran et al, 2015). WSN-GFP was amplified and titered on HA-MDCK cells (Marsh et al, 2007).…”
Section: Virusesmentioning
confidence: 99%